(untitled) (REMUNOM, 2025)
The primary objective of this study lies in the analysis of the advances achieved and the remaining challenges concerning the full realization of the rights inherent to persons with disabilities within the Brazilian labor context. This assessment is conducted in light of two unquestionable normative frameworks: Law No. 8,213/1991 (Quota Law) and Law No. 13,146/2015 (Statute of Persons with Disabilities). Methodologically, the work was conceived and structured based on an exhaustive and rigorous bibliographical and documentary review, through a detailed examination of specialized literature (scientific articles), current legislation, and the analysis of official statistical data provided by governmental institutions (IBGE, MTE).The results obtained unequivocally demonstrate that the robust legal framework has acted as an essential driver of inclusion, inducing a remarkable increase in the number of formal admissions and, more crucially, promoting the legal consolidation of the social model of disability. This paradigm redefines the focus, shifting the notion of individual incapacity to the inalienable responsibility of society in eliminating barriers. Nevertheless, the observed effectiveness of these norms proves to be partial. The main obstacles opposing full inclusion consist of the still incomplete compliance with the established quotas, the evident gap in professional qualification (a direct result of historical educational exclusion), the chronic lack of full accessibility, and, above all, the persistent and stubborn presence of attitudinal barriers crystallized in the phenomenon of ableism.In summary, it is concluded that, although the progress achieved in both normative and quantitative dimensions is irrefutable, substantial inclusion still remains a goal to be attained. Its realization invariably requires the profound overcoming of cultural barriers and the firm adherence to complementary policies and good corporate practices capable of transforming mere legal obligation into an authentic and unconditional culture of inclusion, ensuring not only access but also sustainable permanence and full career development for persons with disabilities.